Maintenance of children's teeth to prevent dental caries - Hamzah, Hayatunnufus (BKM Public Health and Community Medicine, 2021)
Objective : Optimizing dental health programs in schools by working with parents to achieve dental and oral health goals so that children can and are willing to brush their teeth the right way. Content : efforts can be made to instill habits in maintaining children's dental health so that children are expected to be caries-free. As for the challenges faced, namely the difficulty of getting children to want to brush their teeth, besides that parents are sometimes impatient in teaching children and also some do not really care about children's dental health. Lack of parental knowledge of the importance of maintaining children's dental health can also be a factor that can trigger parents not to care about this. whereas, early treatment will minimize the costs incurred if the child has a toothache that requires repeated visits. whereas, early treatment will minimize the costs incurred if the child has a toothache that requires repeated visits. Conclusions: It is hoped that the development of good cooperation between all parties will enable each child to perform their dental care optimally. Making habits such as (brushing teeth) a necessity that will always be done. and children are willing to brush their teeth voluntarily without coercion from their parents and teachers